The influence of digitalisation on the role of quality professionals and their practices - Jason Martin; Quoc Hung Dang; Ida Gremyr (Cogent Business & Management, 2023)
Studies suggest that quality management professionals need a range of skills to simultaneously exploit current operational models and explore digital transformation. However, there is limited research on the impact of digitalisation on improvement work, associated practices and the skills and competencies of quality management professionals. To contribute to this gap, this study draws on a framework based on a conceptual combination of the principles of quality management and the field of occupational competence. The study aims to understand how digitalisation influences the role of quality management professionals, by assessing its influence on the professionals' improvement practices. The study employs a multiple cross-case research design with data from interviews with nine interviewees, and two focus groups. The results show a so far nascent and limited influence of digitalisation on improvement practices, a need for explorative and team-based practices. Moreover, nine needed skills areas to enhance the professionals' potential to benefit from digitalisation in improvement work are suggested. These are Integrator, Pragmatic approach based on a good understanding of possibilities, Change management, Process management, General project management, Improvement analysis, Predictive and proactive approach in QM, General IT and Big data proficiency.
Keywords: 650; Competence; Digitalisation; Digitisation; Improvement Work; Quality Management; Quality Professionals